jurnal Management Strategic PT Tunas Baru Lampung Tbk's Palm Oil Segment 2025–2029 Downstream, Sustainability (ISPO), and Digitalization PKS Operation: Management Strategic PT Tunas Baru Lampung Tbk's Palm Oil Segment 2025–2029 Downstream, Sustainability (ISPO), and Digitalization PKS Operation - Suksmanantyo; Suheriyanto; Wahyudi, Brian Fitri; Yulianto; hidayat , M Taufiq; Hariastuti, Ni Luh Putu (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study examines the 2025–2029 strategic framework for PT TunasBaru Lampung Tbk’s Palm Oil Mill (PKS), focusing on operationalefficiency, ISPO-based sustainability, and digital transformationthrough ERP, MES, and predictive maintenance. Driven by CPO pricevolatility, environmental pressures, and rising transparencydemands, the research applies a mixed-method approach combiningSWOT, BSC, and AHP. SWOT highlights strong vertical integrationbut identifies inefficiencies such as high downtime and energy use,while external opportunities include biodiesel policies, POME biogaspotential, and ESG trends. BSC translates strategic goals intoperformance measures, and AHP (CR = 0.015) prioritizes initiativesobjectively. Overall, the findings emphasize the need for anintegrated, technology-driven strategy to strengthen competitivenessand long-term sustainability.